1998
DOI: 10.1007/s005950050187
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis in esophageal cancer patients with postoperative complications

Abstract: We investigated the relationship between postoperative complications and prognosis in esophageal cancer patients. Two hundred five patients with esophageal cancer were divided into three case groups. Group A (n = 100) consisted of cases without postoperative complications. Groups B (n = 58) and C (n = 47) consisted of cases with minor and major postoperative complications. The 5-year survival rates were 41.8%, 21.3%, and 20.2% in groups A, B, and C, respectively. There was a significant difference in the progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 19 publications
3
69
0
1
Order By: Relevance
“…Major perioperative morbidities may not have a significant effect on long-term survival due to the high-volume of esophagectomys performed at our institution ( Figure 2 However, it has been reported that postoperative infections do have a negative impact on longterm survival in major gastro-intestinal cancer resections 16,17 . In a study conducted by Lerut and colleagues on the impact of postoperative complications after transthoracic esophagectomy using the modified Clavien classification, similar results were reported that there was no difference in survival curves between grades 2, 3, and 4 complications 5 .…”
Section: Discussionmentioning
confidence: 94%
“…Major perioperative morbidities may not have a significant effect on long-term survival due to the high-volume of esophagectomys performed at our institution ( Figure 2 However, it has been reported that postoperative infections do have a negative impact on longterm survival in major gastro-intestinal cancer resections 16,17 . In a study conducted by Lerut and colleagues on the impact of postoperative complications after transthoracic esophagectomy using the modified Clavien classification, similar results were reported that there was no difference in survival curves between grades 2, 3, and 4 complications 5 .…”
Section: Discussionmentioning
confidence: 94%
“…Many researchers have reported that postoperative surgical and medical complications may contribute to a high rate of recurrence and unfavorable long-term survival in various malignancies such as cervical, colorectal and esophageal cancer (3)(4)(5). Increasing evidence has shown that postoperative complications due to infection, especially those caused by anastomotic leakage after colorectal surgery, were significantly associated with a negative long-term outcome (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we did not analyze the effect of other perioperative comorbidities related to blood transfusions, such as postoperative infection, which had been suggested as playing a role in the postoperative rate of cancer recurrence. 42 Furthermore, we did not analyze the effect of any blood transfusion vs no blood transfusion on cancer recurrence. In a meta-analysis, Amato and Pescatori 43 showed a detrimental association between the use of blood transfusion and outcome in patients with colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%